Novel water-based antiseptic lotion demonstrates rapid, broad-spectrum kill compared with alcohol antiseptic - Steven E. Czerwinski; Jesse Cozean; Colette Cozean (Elsevier, 2014)
Summary: A novel alcohol-based antiseptic and a novel water-based antiseptic lotion, both with a synergistic combination of antimicrobial ingredients containing 0.2% benzethonium chloride, were evaluated using the standard time-kill method against 25 FDA-specified challenge microorganisms. The purpose of the testing was to determine whether a non-alcohol product could have equivalent rapid and broad-spectrum kill to a traditional alcohol sanitizer.Both the alcohol- and water-based products showed rapid and broad-spectrum antimicrobial activity. The average 15-s kill was 99.999% of the challenge organism for the alcohol-based antiseptic and 99.971% for the water-based antiseptic. The alcohol-based product demonstrated 100% of peak efficacy (60 s) within the first 15 s, whereas the water-based product showed 99.97%. The novel alcohol-based antiseptic reduced concentrations of 100% of organisms by 99.999%, whereas the water-based antiseptic lotion showed the same reduction for 96% of organisms.A novel water-based antiseptic product demonstrated equivalent rapid, broad-spectrum antimicrobial activity to an alcohol-based sanitizer and provided additional benefits of reduced irritation, persistent effect, and greater efficacy against common viruses. The combination of rapid, broad-spectrum immediate kill and persistent efficacy against pathogens may have significant clinical benefit in limiting the spread of disease. Keywords: Benzethonium chloride, Broad-spectrum antimicrobial activity, Persistence, Hand sanitizer